Decentralized and hybrid trials in oncology: Results of a global survey of clinical research executives. Issue 28 (1st October 2022) - Beg, Shaalan Shaalan; Bustos, Drew
Abstract : 102 Background: Decentralized (DCT) and hybrid (Agile) clinical trials have the potential to deliver significant enhancements to trial operations by improving access to patients and providers. We conducted a survey of research executives at sponsor sites and contract research organizations (CRO) to understand trends in oncology clinical trials. Methods: The survey took place in March and April 2022 via online questionnaires. Only complete responses from senior executives who are either involved in sponsoring or managing clinical research within oncology, or who are planning to execute oncology clinical trials in future, were included. Response data were analyzed by an independent market research service and tested for significance at the 95% confidence level. Results: The questionnaires generated a "qualified" respondent sample of 85 responses. Most (60%) respondents were from biopharmaceutical sponsors, with around one-third from organizations with more than US20 billion in revenue. The most frequent perceived challenges for oncology clinical trials execution were patient recruitment (72% of execs ranked this in their top 3); study start-up (55%); and study delays (54%). Three in four executives (73%) are planning to run either a DCT or hybrid trial for oncology in the next 12 months, up significantly from 49% in the prior 12 months. Most common cancer indications for DCT in the next 12 months are lung cancer (40%), leukemia/blood cancers (37%), and breast cancer (30%). More than half of respondents reported that they plan to include ePRO/eCOA tools (57%) and telemedicine (54%) in their oncology clinical trial designs over the next 12 months. A further 48% expect to deploy Mobile Nurses, with the same number planning to incorporate eConsent. The top three perceived benefits of using DCT tools identified in oncology trials are increased patient retention (67%); greater patient diversity (54%); and faster patient recruitment (50%). Conclusions: The survey of oncology research executives highlights the most common perceived challenges in executing clinical trials. Many of these challenges can be addressed using decentralized tools. Researchers are planning to significantly increase the adoption of DCT in the coming year. DCT adoption in oncology clinical trials Prev 12 mos Next 12 mos Traditional, Site-Based Trial 88% 65% Agile Trial (Hybrid) 43% 58% Fully Decentralized Trial 19% 40% Agile Trial OR Fully Decentralized Trial 49% 73%.